Tradisi Penyusun Kamus Arab - Akhmad Saehudin (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2005)
For the first time, the language was only developed on an oral tradition. Then, it appeared a written tradition in order to keep its language survival. Its supporting instrument is the tradition of writing dictionary (Lexicography). The Dictionary in the Arab world looks very unique because the linguists had arranged it in various forms.